Pengaruh Gaya Komunikasi Pendamping Terhadap Tingkat Kepuasan Peserta UMKM Naik Kelas Kota Bekasi - Riana Astuti; Nicha Muslimawati (Yayasan Riset dan Pengembangan Intelektual, 2025)
Micro, small, and medium enterprises (MSMEs) are a strategic sector for the national economy due to their role in providing employment, fostering business innovation, and supporting community economic resilience. This study aims to describe the communication style of facilitators in the “UMKM Naik Kelas” program, analyze participant satisfaction, and examine the effect of facilitator communication style on participant satisfaction in Bekasi City. A quantitative survey was conducted with 100 program participants using a Likert-scale questionnaire (1–5) that was validated and tested for reliability. Data were analyzed descriptively and using simple linear regression. Results indicate that facilitators’ communication is generally good in terms of clarity, empathy, and material relevance, while motivation and responsiveness need improvement. Participant satisfaction is very high across process, outcomes, and services. Regression analysis shows a positive and significant effect of communication style on participant satisfaction (coefficient 0.271; R² 12.4%). It is recommended that facilitators enhance motivation, responsiveness, and communication style variation to increase program effectiveness.